Kerangka Partisipan dalam Video Youtube Puja Astawa - Novita Mulyana; Yana Qomariana (Udayana University, 2023)
Puja Astawa is one of Balinese famous YouTube content creators. His videos display interactions, mostly informal ones, and they are favored by the Balinese not only due to the humor contains in the videos, but also because of the moral values and the messages conveyed in the video. Puja Astawa often raised current issues in the society as the topics for his videos. It makes the interactions displayed in the video real-life like and reflects the real life of a Balinese. Due to this real-life likeness, his videos are interesting to be discussed further, especially in linguistics points of view. This study was conducted in order to identify and analyze the type of participation framework reflected in social interactions in the videos. In order to achieve the aim of the study, this qualitative study selected thirteen Puja Astawa’s videos as the source of the data. Those videos are selected based on several criteria, namely (1) the video was uploaded in 2021 until June 2022, (2) the duration of the video is more than four minutes, and (3) there are more than two participants in the video. In collecting the data, documentation method and note taking technique were utilized. The collected data were then analyses based on participation framework theory which is proposed by Goffman. The result of the analysis shows that the utterance uttered by the participants in the videos reflects the participation framework. All of the participants are the animator of their utterance. However, not all of the participants are the author, figure or the principal of their utterance. There are many things that may contribute to this finding, one of them in the nature of the video which is a scripted interaction